REVISITING THE ORGANIZATION OF A CLINICAL (MEDICAL) PSYCHOLOGIST WORK AT THE FIRST STAGE OF MEDICAL REHABILITATION IN THE CONDITIONS OF THE INTENSIVE CARE UNIT (ICU) BY THE EXAMPLE OF REGIONAL VASCULAR CENTRE (RIC) - Слекишина, Алена Валентиновна; Жестикова, Марина Григорьевна; Зиборова, Светлана Станиславовна (Medicine in Kuzbass, 2025)
The aim of the research – determining the optimal working environment for a clinical (medical) psychologist at the first stage of medical rehabilitation in the conditions of the intensive care unit (ICU). Finding the way to maintain a qualitative analysis of higher mental functions while reducing working hours adequately.Materials and methods. Theoretical analysis of sources and literature, Russian Ministry of Health Decree of 31 July 2020 № 788N on approval of the procedure of organizing of medical rehabilitation for adults.Results. Somatic condition of a patient in the ICU is defined as severe. Consequently, the number of working hours with such a patient is relatively restricted. During the first stages of  medical rehabilitation neurophysiological diagnostics should form a full understanding of a patient's condition in order to identify the purpose of medical rehabilitation. At the same time, neurophysiological diagnostics should be comprehensive regardless limited working hours. Nowadays there are no neurophycological diagnostic tools in those cases when the duration of the examination can't be long.Conclusion. There is currently a pressing need to devise a way of neurophycological diagnostics of higher mental functions which would allow to detect cognitive impairment in patients in the ICU during the first stages of medical rehabilitation taking into account working hours constraints.
Keywords: medical rehabilitation; medical psychologist; neurophycological diagnostics; higher mental functions